Aspectos teórico-numéricos dos métodos SPH e MPS - Takata, Adriano Sueke [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Currently, due to the technological advances the use of particle methods is gaining ground in the simulations of fluid flow. The first particle method to be developed was the Smoothed Particle Hydrodynamics (SPH) that was very efficient for compressible flow problems, but inefficient for incompressible ones. Thus, there was some strategy to solve incompressible flow problems as the incompressible Smoothed Particle Hydrodynamics (ISPH) and the Moving Particle Semi-Implicit (MPS); in both methods the pressure is updated by a Poisson equation. For an approximation of the Navier-Stokes equations it is first needed a good approximation for the Poisson equation. This paper discusses the following particles methods: Smoothed Particle Hydrodynamics (SPH) and Moving Particle Semi-Implicit (MPS). The discretization of differential operators by these methods is done through the approximation of the kernel and also by particles. A comparative study of different discretizations were made. In order to know if the parameters used in the literature for the SPH and MPS methods provide a good solution for Poisson equation, have been performed several tests by varying the parameters with and without the borders treatment. This work also proposed a strategy to solve the oscillation problem in advection equation with discontinuity in the initial conditions and the results were very satisfactory

Atualmente, devido ao grande avanço tecnológico o uso dos métodos de partículas vêm ganhando espaço nas simulações de escoamento de fluido. O primeiro método de partículas a ser desenvolvido foi o Smoothed Particle Hydrodynamics (SPH) que se mostrou bastante eficiente para problemas de escoamento compressível, mas ineficiente para escoamento incompressível. Desta forma, surgiu algumas estratégias para resolver problemas de escoamento incompressível como o Incompressible Smoothed Particle Hydrodynamics (ISPH) e o Moving Particle Semi-Implicit (MPS); em ambos os métodos a pressão é atualizada por um equação de Poisson. Portanto para obter uma boa aproximação das equações de Navier-Stokes é necessário antes ter uma boa aproximação da equação de Poisson. Neste trabalho são abordados os métodos de partículas Smoothed Particle Hydrodynamics (SPH) e Moving Particle Semi-Implicit (MPS). A discretização dos operadores diferenciais por esses métodos é feita por meio da aproximação do núcleo e também por partículas. Um estudo comparativo entre discretização foram efetuadas. Afim de saber se os parâmetros utilizados na literatura dos métodos de partículas SPH e MPS dão uma boa solução para equação de Poisson foram realizados vários testes variando os parâmetros com e sem o tratamento de fronteira. Neste trabalho também foi proposta uma estratégia para resolver o problema de oscilação na solução da equação de advecção com descontinuidade nas condições iniciais e os resultados foram bem satisfatório
Keywords: Computação - Matematica; Particulas; Hidrodinâmica - Programas de computador; Computer science - Mathematics